2022
DOI: 10.21203/rs.3.rs-2050019/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The emergence of categorical norms

Abstract: Why are norms unduly sensitive to categorical distinctions compared to continuous variation? For instance, the norm against the use of chemical weapons considers the type of weapon used, not how much suffering was caused; human rights are conditioned on membership in the species homo spaiens not on an animal's degree of sentience; norms promoting philanthropy emphasize donating, and are relatively insensitive to the impact a donation will have. Here we present a game theoretic model, which explains why it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…We found that the framing of actions (active versus passive harm) mainly influenced judgments, whereas selfish actions were less framing-sensitive and depended on the varying choice outcomes instead. This refines theoretical proposals that coordination on what constitutes a norm transgression relies on categorical distinctions between the general nature of actions, rather than continuous outcomes considerations (23). Our analysis shows that although normative judgments may be considered categorical, actions are often more nuanced and depend on decision stakes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We found that the framing of actions (active versus passive harm) mainly influenced judgments, whereas selfish actions were less framing-sensitive and depended on the varying choice outcomes instead. This refines theoretical proposals that coordination on what constitutes a norm transgression relies on categorical distinctions between the general nature of actions, rather than continuous outcomes considerations (23). Our analysis shows that although normative judgments may be considered categorical, actions are often more nuanced and depend on decision stakes.…”
Section: Discussionsupporting
confidence: 81%
“…Our results additionally contribute to the debates on the nature of social preferences, and in particular the importance of contexts (23), outcome-based preferences (24,25), and unconditional moral preferences (79). By using a combination of varying outcome ranges and utility models, we could capture the effects of different motives at the individual level within the same framework.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation